Kemampuan Berpikir Kritis Siswa Kelas X Pada Materi Atmosfer Dengan Menggunakan Media Handout Berbasis Flip Html5 Di Sman 36 Jakarta - Anggraini, Dea Nur; Sya, Ahman; Hardi, Ode Sofyan (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to determine the effect of handout based on Flip HTML5 on the critical thinking skills of class X students on atmosphere material at SMAN 36 Jakarta. Data collection was carried out for four weeks from March to April 2023 with a total sample of 68 students. The sampling technique in this study used the probability sampling method which consisted of 34 students from class X E5 as the experimental class and 34 students from class X E6 as the control class. The method used is an experiment with a pretest-posttest control group design. Based on the results of the study, it was found that the experimental class had higher learning outcomes than the control class. The results of the posttest hypothesis test using the Independent Sample T-Test at a significance level of 0.05 obtained a significance (2-tailed) of 0.029. This shows that the rule of decision that can be taken is that H0 is rejected and Ha is accepted, meaning that there is an influence of handout based on Flip HTML5 on the critical thinking skills of class X students on atmosphere material at SMAN 36 Jakarta. Based on the calculation of student response questionnaires in the experimental class to handout based on Flip HTML5, a score of 86.70% was obtained and was in the very good category. The use of handout based on Flip HTML5 during learning activities in the experimental class was considered capable of training students' critical thinking skills by providing materials, learning videos, as well as several assignments to solve a problem or phenomenon.